Polyclonal activation to immunoglobulin secretion in human adenoid lymphocytes induced by bacteria from nasopharynx in vitro - Rynnel-Dagöö, Britta (1978)
Adenoid lymphocytes from twenty-six children scheduled consecutively for adenoidectomy because of severe nasal obstruction were stimulated in vitro by D. pneumoniae, H. influenzae and haemolytic streptococci group A. All bacteria induced both increased DNA synthesis and polyclonal antibody secretion, tested in a haemolytic plaque assay. The magnitude of the B-cell response was correlated to the age of the children. Thus, cells from older children showed a significantly higher polyclonal response than those from younger children. No case of unresponsiveness to any stimulant was observed. Susceptibility to infection was more pronounced among the younger children, which might reflect some degree of immaturity in the immune system. However, adenoid lymphocytes are immunocompetent cells, contributing to antibody secretion in the response against infection. The role of the receptor for PBA substances on adenoid cells in immune reactions against infectious micro-organisms is discussed.